Analisis Faktor yang Mempengaruhi Kualitas Pelayanan Konseling KB AKDR oleh Bidan di Wilayah Kerja Puskesmas Wiradesa Kabupaten Pekalongan Tahun 2013 - Nuning Arsyaningsih; Suhartono Suhartono; Titi Suherni (JURNAL KEBIDANAN, 2014)
Issues relating KB IUD because of low coverage based on the findings of a qualitative field health center midwives tend to pay less attention to the pre counseling and counseling at the time of IUD insertion so much lack of information supplied accessories midwife makes the lack of knowledge about the IUD acceptors and the assumption or assumption in the community about the loss / effects IUD side is less capable in clarification by health workers, especially midwives is necessary to do research on factors that affect the quality of service farkor planning counseling intrauterine device (IUD) by a midwife at health center of Wiradesa Pekalongan in 2013.This research is quantitative. The study population was a midwife who Puskesmas Wiradesa totaling 33 midwives with univariate and bivariate analysis of the independent variables and the dependent variable with the aim to analyze the factors that affect aspects (physical evidenc) of tangible, reliability, responsiveness, assurance and empathy toward family planning counseling service quality of an intrauterine device (IUD) by a midwife.The results showed the p value of 0.05 obtained the following results: no influence on the tangible aspects of counseling with a significance value of 0.000, the reliability of the counseling with a significance value of 0.000, responsiveness to counseling with a significance value of 0.010, assurance against counseling with a significance value of 0.000, empathy to counseling with a significance value of 0.000.            Suggested need to improve co-operation with professional organizations IBI and midwifery education institutions in Pekalongan to jointly establish procedures IUD contraception counseling services counseling training curriculum improvement planning services / KIP with the use and installation of updates ABPK contraceptive IUD (CopperT).